Gender bias in the news: On diversity and the democratic role of the Media - Jóhannsdóttir, Valgerður; Steinþórsdóttir, Finnborg Salome (Stjórnsýslustofnun, 2022)
The media plays a key role in democratic societies. Democracy requires people to have access to information and discussion on societal issues. The responsibility of the media is great and according to Icelandic legislation, the media must ensure that the views of both men and women are expressed and work towards equality and equal opportunities for all genders. Iceland, like other Nordic countries, has been at the top of international lists on gender equality for many years. The objective of this paper is to examine how the Icelandic media reflects this. How diverse is the news in and how does Iceland compare with the other Nordic countries? Based on data collected in the Gender and Media Monitoring Project in 2020 we argue that the Icelandic media is more biased towards men than might be expected based on the position of women in Icelandic society in general. Only a third of interviewees in the news are women and women´s proportion is lower than in other Nordic countries. Women are however not interviewed less than men in so-called “hard” news. The proportion of women interviewed in domestic news has increased significantly compared to previous studies, but it is still low in foreign news. Few women are in the role of experts in the news, which is not in line with women‘s position in society. The results indicate that measures need to be taken to promote equality and diversity in the media if the media is to fulfil its democratic role. Fjölmiðlar gegna mikilvægu hlutverki í lýðræðissamfélögum. Lýðræði krefst þess að fólk hafi aðgang að upplýsingum og umræðu um samfélagsleg málefni. Það sem fjölmiðlar birta skiptir máli og lögum samkvæmt ber þeim að gæta þess að sjónarmið jafnt karla sem kvenna komi fram og að vinna að jafnrétti og jöfnum tækifærum allra kynja. Ísland, líkt og önnur Norðurlönd, hefur í fjölmörg ár verið ofarlega á alþjóðlegum listum um kynjajafnrétti. Markmið þessarar greinar er að skoða hvernig íslenskir fjölmiðlar spegla það. Hversu fjölbreyttar eru fréttirnar og hvernig stendur Ísland í ...